IMF Staff papers : Volume 15 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1968)
An earlier version of this paper was presented to a conference on the topic 'Is the Business Cycle Obsolete?' organized by the Social Science Research Council and held in London, England, on April 3-7, 1967.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet